2018
DOI: 10.1093/ndt/gfy139
|View full text |Cite
|
Sign up to set email alerts
|

Quality over quantity? Association of skeletal muscle myosteatosis and myofibrosis on physical function in chronic kidney disease

Abstract: In CKD, increased US-derived EI was negatively correlated with physical performance; however, muscle size remains the largest predictor of physical function. Therefore, in addition to the loss of muscle size, muscle quality should be considered an important factor that may contribute to deficits in mobility and function in CKD. Interventions such as exercise could improve both of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 51 publications
(119 reference statements)
2
67
1
Order By: Relevance
“…Rectus femoris anatomical cross-sectional area (CSA) was determined using B-mode 2-D ultrasonography (Hitachi EUB-6500; probe frequency 7.5 MHz) as previously described 32,41,42 and has recently been validated against MRI 43 . Images were captured at the mid-point between the greater trochanter and the superior aspect of the patella on the midsagittal plane of the thigh.…”
Section: Quadriceps Muscle Sizementioning
confidence: 99%
“…Rectus femoris anatomical cross-sectional area (CSA) was determined using B-mode 2-D ultrasonography (Hitachi EUB-6500; probe frequency 7.5 MHz) as previously described 32,41,42 and has recently been validated against MRI 43 . Images were captured at the mid-point between the greater trochanter and the superior aspect of the patella on the midsagittal plane of the thigh.…”
Section: Quadriceps Muscle Sizementioning
confidence: 99%
“…Importantly, quadriceps muscle size and function is well recognized as an important contributor to reduce exercise capacity and increase morbidity and mortality in chronic disease populations . Indeed, we have recently shown that RF‐CSA measured by ultrasound is independently associated with physical performance measures amongst non‐dialysis CKD patients . Therefore, being able to quickly and accurately quantify changes in lower limb muscle that are functionally important—such as RF—is of particular interest to clinicians and researchers.…”
Section: Discussionmentioning
confidence: 99%
“…9,23 Indeed, we have recently shown that RF-CSA measured by ultrasound is independently associated with physical performance measures amongst non-dialysis CKD patients. 21 Therefore, being able to quickly and accurately quantify changes in lower limb muscle that are functionally important-such as RF-is of particular interest to clinicians and researchers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations